Economic Growth, Youth Unemployment and Poverty in Nigeria: A Granger Causality Approach - Omoyele, Olufemi Samuel; Oloke, Emmanuel; Olabisi, Faseesin; Aderemi, Timothy Ayomitunde (Acta Universitatis Danubius. Œconomica, 2022)
The aim of this study is to examine the direction of causality among economic growth, unemployment and poverty in Nigeria. In the recent times, the cases of youth unemployment have been on the increase in developing countries, especially in Nigeria. This is due to the fact that the youth population is rising at an alarming rate comparing to the rate at which economic growth is expanding. Meanwhile, there is little or no empirical evidence to establish a meaningful impact of economic growth on youth employment and poverty in Nigeria. Against this backdrop, this study examined a causal relationship been between economic growth, unemployment and poverty in Nigeria between 1990 and 2019. Consequently, the findings that emerged in this could be summarized as follows. There was no directional causality between youth unemployment and economic growth in Nigeria Similarly, no evidence to support the direction of causality between economic growth and poverty in Nigeria. However, unidirectional causality runs from poverty to youth unemployment in Nigeria. This implies that youth unemployment in Nigeria was largely motivated by high level of poverty in the country. In the light of the above findings, this study therefore makes the following recommendations for the policymakers in Nigeria that any time these policymakers want to address the problem of youth unemployment in the country, policy that will reduce poverty level should be embarked upon. Also, policy that stimulates economic growth should be encouraged in Nigeria